(untitled) (Global Journal of Human-Social Science, 2021)
This study reports the find ings of a research carried in Nakivale refugee settlement, south western Uganda. The paper argues that self-reliance for refugees have reduced donors’ fatigue and encouraged refugees to engage in different economic activities that have enabled them to be economically independent from donors specifically United Nations High Commissioners for Refugees (UNHCR) and its implementing partners like the World Food Programme (WFP). The study therefore was to examine the factors influencing refugee dependence on handouts/humanitarian aid in Nakivale settlement by identifying how refugees cope up in the settlement. The researcher adopted both quantitative and qualitative research designs in the collecting and analyzing data. Data were analyzed by use of descriptive statistics, multinomial logistic regression and description of themes. The findings revealed that; majority of the households depend on handouts from UNHCR/WFP, and vulnerability to sexual harassment significantly affects refugees’ dependency on handouts.